Polymicrobial candidaemia revealed by peripheral blood smear and chromogenic medium. Issue 2 (27th January 2004) - Yera, H; Poulain, D; Lefebvre, A; Camus, D; Sendid, B
Abstract : Candida spp are the fourth most common group of nosocomial pathogens isolated from patients on medical, surgical, and intensive care wards. Polymicrobial candidaemia has rarely been described. The diagnosis of candidaemia from peripheral blood smears has not been widely reported. This report describes the case of a young woman suffering from Ewing's sarcoma who developed a syndrome of septic shock. Deep fungal infection was diagnosed from a systematic peripheral blood smear and yeasts were isolated within 24 hours. A subculture on CHROMagar® Candida allowed the differentiation and presumptive identification of Candida tropicalis and Candida krusei . Species identification was confirmed by the ID 32C® system. This report underlines the usefulness of peripheral blood smears in the diagnosis of fulminant deep fungal infections, and of a differential isolation medium in the rapid presumptive identification of clinically important yeast species from clinical samples. This medium is particularly useful for the detection of mixed fungal infections, allowing early and better adapted antifungal treatment.